Pectin extraction from lime pomace by cold-active polygalacturonase-assisted method - Bezus, Brenda; Contreras Esquivel, Juan Carlos; Cavalitto, Sebastian Fernando; Cavello, Ivana Alejandra (International Journal of Biological Macromolecules)
An Antarctic yeast was cultivated to produce and enzymatic extract with polygalacturonase activity, whose biochemical properties were studied. It assisted pectin extraction from lime pomace at 20 °C. The extract produced by Tausonia pullulans 8E had an optimum temperature of 40 °C and optimum pH of 5.0. At 20 °C, it displayed 54% of relative activity. A good pH-stability and thermostability were observed. Hg+2 and Co+2 inhibited its activity in 40 and 11%, respectively. Pectin was obtained from lime pomace at 20 °C, with 15% of yield after 120 min extraction. Uronic acid (46%) and neutral sugars (53%) were determined. Pectin's molecular weight was estimated in the order of 100,000 g mol−1. By anion-exchange chromatography, pectin-linked and free neutral sugars were observed. The high-methoxyl pectin was used to prepare low-calorie gels. It was demonstrated that this cold-active enzyme allows enzymatic-assisted pectin extraction at 20 °C. Fil: Bezus, Brenda. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Investigación y Desarrollo en Fermentaciones Industriales. Universidad Nacional de La Plata. Facultad de Ciencias Exactas. Centro de Investigación y Desarrollo en Fermentaciones Industriales; Argentina Fil: Contreras Esquivel, Juan Carlos. Universidad Autonoma de Coahuila; México Fil: Cavalitto, Sebastian Fernando. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Investigación y Desarrollo en Fermentaciones Industriales. Universidad Nacional de La Plata. Facultad de Ciencias Exactas. Centro de Investigación y Desarrollo en Fermentaciones Industriales; Argentina Fil: Cavello, Ivana Alejandra. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Investigación y Desarrollo en Fermentaciones Industriales. Universidad Nacional de La Plata. Facultad de Ciencias Exactas. Centro de Investigación y ...